2022
DOI: 10.1039/d2tc01140a
|View full text |Cite
|
Sign up to set email alerts
|

Control of molecular conductance by pH

Abstract: pH plays a fundamental role in regulating various processes occurring in ecosystems, biological organisms, and chemistry laboratories, and lately, has been observed to drastically impact material electronic properties at the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…It is necessary to develop strategies to enhance the nucleation and prevent the growth or agglomeration of large particles during synthesis, as discussed, e.g., in a recent topical review. [ 120 ] Alternative approaches to controlling the grain sizes may include low‐temperature post‐treatment, porous‐electrode templating [ 121 ] or mechanochemical synthesis. [ 122 ] 2)Developing mild but high‐yield synthesis: Non‐noble TMOs are desirable as alternatives for precious metal Ru‐/Ir‐based oxides due to low cost of chemical resource.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to develop strategies to enhance the nucleation and prevent the growth or agglomeration of large particles during synthesis, as discussed, e.g., in a recent topical review. [ 120 ] Alternative approaches to controlling the grain sizes may include low‐temperature post‐treatment, porous‐electrode templating [ 121 ] or mechanochemical synthesis. [ 122 ] 2)Developing mild but high‐yield synthesis: Non‐noble TMOs are desirable as alternatives for precious metal Ru‐/Ir‐based oxides due to low cost of chemical resource.…”
Section: Discussionmentioning
confidence: 99%
“…Catalyst Synthesis : The NiFe LDH/Vulcan was synthesized through a one‐step hydrothermal method [26,28] . 0.6 mmol nickel sulfate, 0.3 mmol ferrous sulfate, 0.06 mmol trisodium citrate and 1.6 mmol urea were dissolved in 10 mL Milli‐Q water.…”
Section: Methodsmentioning
confidence: 99%
“…Once the self-assembled structure is created, the changes in environmental conditions may cause consequences for the assembling outcomes. [105][106][107][108][109] Recently, it has been reported that stimulus of external conditions allows supramolecules to grow a second layer on top of the already-grown monolayer. An interesting example is the TPTC bilayer selectively grown by an annealing treatment for 1 min at the nonanoic acid/ HOPG interface.…”
Section: Benzene Carboxylic Acidsmentioning
confidence: 99%